Komparasi Efektivitas PAC dengan Biokoagulan Musa paradisiaca L. pada Limbah Cair Industri Tahu - Mendrofa, Cynthia Alvionie Erza; Adzillah, Wilma Nurrul; Mentari, Okti Dinasakti Nurul (Universitas Tanjungpura, 2025)
The peel of Kepok banana (Musa paradisiaca L.) can be utilized as an environmentally friendly coagulant in the treatment of tofu industry wastewater. This study examined the effectiveness of the bio-coagulant derived from Kepok banana peel in comparison to the chemical coagulant Poly Aluminium Chloride (PAC) in reducing pollutant concentrations in the tofu industry